Un Millón de Chilenos: Testimonies of the Exile in the Journal Araucaria de Chile ["Un Millón de Chilenos": Testimonios del Exilio en la Revista Araucaria de Chile] - Zamorano-Diaz, C (Universidad de Talca, 2021)
One of the political consequences of the repression experienced during the years of the Chilean dictatorship established after the 1973 coup d état and led by the military Junta, was the phenomenon of exile. Through the study of the journals created by Chileans in exile in the most remote places of the planet, it is possible to recompose the cultural and political history of Chile. In particular, this article proposes cultural journals as fundamental spaces for recognizing how the common experience of a past of Unidad Popular is approached from exile, together with the horror of a present marked by the coup d état, persecution and exile. In this sense, the journal Araucaria de Chile (1978-1990) coined in its pages the writing of the outside, pierced by the modes of saying dependent to a great extent on the concrete experience of the social disarticulation of a previous identity and its ways of re-articulation. Focusing the work on the section "Un millón de chilenos" will allow us to identify three dimensions within the set of testimonial narratives that deal with the experience of exile defined as uprooting, guilt and possibility. © 2021 Universidad de Talca. All rights reserved.